2021
DOI: 10.1042/bsr20201902
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-409-3p promotes osteoblastic differentiation via activation of Wnt/β-catenin signaling pathway by targeting SCAI

Abstract: Osteogenic differentiation is an important process of new bone formation, microRNA-409-3p (miR-409-3p) has been reported to be up-regulated in the osteogenic differentiation of human bone marrow mesenchymal stem cells (MSCs). The present study aimed to investigate the regulatory effect of miR-409-3p on osteogenic differentiation of MSCs and its molecular mechanism. The expression of miR-409-3p in osteoblast (human skull osteoblast, HCO) and bone marrow-derived MSCs (MSC-A, MSC-B, MSC-U) were detected by revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We further measured the expression levels of important factors involved in the regulation of osteoblastic differentiation, such as BMP-2 [ 20 ], Ocn [ 21 ], and ALP [ 22 ]. We found that BMP-2, Ocn, and ALP ( Figure 3a-b ) were significantly upregulated in osteogenic medium-cultured MC3T3‑E1 cells at both the mRNA and protein levels, and pronouncedly further upregulated by 20 μM Omarigliptin, revealing the regulatory function of Omarigliptin on osteoblastic differentiation is associated with these factors.…”
Section: Resultsmentioning
confidence: 99%
“…We further measured the expression levels of important factors involved in the regulation of osteoblastic differentiation, such as BMP-2 [ 20 ], Ocn [ 21 ], and ALP [ 22 ]. We found that BMP-2, Ocn, and ALP ( Figure 3a-b ) were significantly upregulated in osteogenic medium-cultured MC3T3‑E1 cells at both the mRNA and protein levels, and pronouncedly further upregulated by 20 μM Omarigliptin, revealing the regulatory function of Omarigliptin on osteoblastic differentiation is associated with these factors.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-409 has shown to enhance osteogenic differentiation by activating the Wnt-signalling pathway. MiR-409 directly targeted Suppressor of Cancer Cell Invasion, thereby reducing its expression, whereas Suppressor of Cancer Cell Invasion upregulation showed to decrease osteoblastic differentiation and reduce protein expression of Wnt-signalling related genes, such as β-catenin, c-myc, and cyclin D1 (107). A glucose regulated miRNA, miR-451, enhanced osteoblastogenesis in vitro and in vivo, by suppressing Odd Skipped Related 1 whilst enhancing RUNX2 and BMP-4 expression (67).…”
Section: Osteogenesis and Osteoblastogenesismentioning
confidence: 99%
“…miR-409-3p, an unexplored candidate, has been primarily investigated in oncology. For instance, miR-409-3p promotes epithelial to mesenchymal transition and tumor growth in prostate cancer and also accelerates osteoblastic differentiation through the Wnt/ β -catenin pathway [ 17 , 18 ], a crucial pathway in regulating cardiac fibrosis. Previous clinical study discovered its potential value in distinguishing atrial fibrillation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%